Management of invasive well‐differentiated thyroid cancer: An American head and neck society consensus statement: AHNS consensus statement. Issue 10 (23rd August 2014) - Shindo, Maisie L.; Caruana, Salvatore M.; Kandil, Emad; McCaffrey, Judith C.; Orloff, Lisa A.; Porterfield, John R.; Shaha, Ashok; Shin, Jennifer; Terris, David; Randolph, Gregory
ABSTRACT Background Invasive differentiated thyroid cancer (DTC) is relatively frequent, yet there is a paucity of specific guidelines devoted to its management. The Endocrine Committee of the American Head and Neck Society (AHNS) convened a panel to provide clinical consensus statements based on review of the literature, synthesized with the expert opinion of the group. Methods An expert panel, selected from membership of the AHNS, constructed the manuscript and recommendations for management of DTC with invasion of recurrent laryngeal nerve, trachea, esophagus, larynx, and major vessels based on current best evidence. A Modified Delphi survey was then constructed by another expert panelist utilizing 9 anchor points, 1 = strongly disagree to 9 = strongly agree. Results of the survey were utilized to determine which statements achieved consensus, near‐consensus, or non‐consensus. Results After endorsement by the AHNS Endocrine Committee and Quality of Care Committee, it received final approval from the AHNS Council. © 2014 Wiley Periodicals, Inc. Head Neck, 36: 1379–1390, 2014